2015
DOI: 10.1371/journal.pone.0135410
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Profiling of PARP1 Reveals an Interplay with Gene Regulatory Regions and DNA Methylation

Abstract: Poly (ADP-ribose) polymerase-1 (PARP1) is a nuclear enzyme involved in DNA repair, chromatin remodeling and gene expression. PARP1 interactions with chromatin architectural multi-protein complexes (i.e. nucleosomes) alter chromatin structure resulting in changes in gene expression. Chromatin structure impacts gene regulatory processes including transcription, splicing, DNA repair, replication and recombination. It is important to delineate whether PARP1 randomly associates with nucleosomes or is present at spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 87 publications
3
58
0
Order By: Relevance
“…CTCF has emerged as an important cofactor of the host protein PARP1 (Farrar et al, 2011; Ong et al, 2013; Nalabothula et al, 2015; Zhao et al, 2015). We hypothesized that PARP1 and CTCF may cooperate at the BZLF1 promoter to collectively restrict EBV lytic reactivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CTCF has emerged as an important cofactor of the host protein PARP1 (Farrar et al, 2011; Ong et al, 2013; Nalabothula et al, 2015; Zhao et al, 2015). We hypothesized that PARP1 and CTCF may cooperate at the BZLF1 promoter to collectively restrict EBV lytic reactivation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work in the PARP field has revealed new functions for PARP1 beyond its enzymatic activity (Zhao et al, 2015; Nalabothula et al, 2015). We hypothesized that in the context of EBV lytic reactivation, PARP1 binding may be more relevant than its activity.…”
Section: Resultsmentioning
confidence: 99%
“…Though PARP1 is usually studied in the context of DNA damage sensing and repair, it has also been associated with the regulation of gene expression (Ogino et al, 2007) and with active chromatin and regions with regulatory potential as assayed by DNase I hypersensitivity (Nalabothula et al, 2015). More specifically, PARP and Parp1-dependent PARylation have been implicated in gene regulation from distal enhancer elements that are controlled by nuclear hormone receptors including; ecdysone inducible puffs in Drosophila (Sawatsubashi et al, 2004) and the action of the liganded progesterone receptor in mammalian breast cancer cells (Wright et al, 2012).…”
Section: Parp-dependent Chromatin Puffing and Enhancer Activationmentioning
confidence: 99%
“…Furthermore, poly(ADP-ribosyl)ation has been associated with mammalian longevity (Mangerich and Burkle, 2012). Interestingly, genomewide methylation analyses revealed changes in methylation patterns resulting from inhibition of PARylation in breast cancer cell lines, indicating a reciprocal interplay between PARP1 and DNA methylation (Nalabothula et al, 2015). Caiafa and coworkers demonstrated that inhibition of PARylation induces in vivo DNA hypermethylation (de Capoa et al, 1999;Zardo et al, 1997Zardo et al, , 2002 and that CCCTC-binding factor (CTCF) is involved in the cross-talk between poly(ADP-ribosyl) ation and DNA methylation (Guastafierro et al, 2008), suggesting that PAR protects DNA from methylation.…”
Section: Epigenetic Biomarkersmentioning
confidence: 99%